THERMAL EXPANSION OF SOLID STATE - COMPUTER-BASED EXPERIMENT - GERHATOVA, Zaneta (Trends in education, 2014)
In this paper we present the transformation hands-on experiment Thermal expansion of solid state (the original experimental apparatus from NTL Company) to the computer-based experiment. This transformation, we carried out using the control panel Internet School Experimental System (ISES), the temperature sensing module from ISES and a digital indicator from the Mahr Company.
Keywords: hands-on experiment; computer-based experiment; thermal expansion of solid state.